COMPARISON BETWEEN THE EFFECTIVENESS OF THE PICTURE HEALTH WARNING (PHW) AND PICTURE HEALTH WARNING WITH DESCRIPTION (PHWD) SIZE 75 PERCENT OF THE STOP SMOKING INTENTION - Ishomuddin; Ahmad, Miqdad Daly (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to compare differences in the intention of quitting smoking on subjects given cigarette packaging with PHW 75 percent and subjects given cigarette packaging with PHWD 75 percent. This study is a true experiment design, taking male participants 17-26 years old, has consumed more than 100 cigarettes, and still smokes at least 30 days before the experiment with a total of 74 people. This research succeeded to reveal if there is no difference between the intention to stop smoking between PHW 75 percent and PHWD 75 percent. So it can be concluded that the addition of information on PHW with the size of 75 percent is not effective in reducing the intention to quit smoking. It has also revealed that there is no significant difference in perceived effectiveness and fear appeals from PHW and PHWD packaging.